2019
DOI: 10.3390/plants8110509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bactericera cockerelli Herbivory on Volatile Emissions of Three Varieties of Solanum lycopersicum

Abstract: Domesticated tomato (Solanum lycopersicum L.) crops have presented an increased susceptibility to pests under field and greenhouse conditions. Among these pests is tomato/potato psyllid, Bactericera cockerelli Sulc (Hemiptera: Triozidae), a major pest in solanaceous crops. In this study, we evaluated volatile organic compound (VOC) emissions from the headspace in three healthy varieties of tomato plants (Floradade, Micro-Tom and wild) under greenhouse conditions using solid-phase microextraction and gas chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Considerable progress has been made in tomato plant cultivation by characterizing its volatile emissions during herbivore attack and investigating their crucial role in attracting natural enemies (Kant et al, 2004;Mayo-Hernández et al, 2019). However, the genetic basis underlying the constitutive release of VOCs involved in direct and indirect defenses, and their effect on herbivores, are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable progress has been made in tomato plant cultivation by characterizing its volatile emissions during herbivore attack and investigating their crucial role in attracting natural enemies (Kant et al, 2004;Mayo-Hernández et al, 2019). However, the genetic basis underlying the constitutive release of VOCs involved in direct and indirect defenses, and their effect on herbivores, are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…We characterized the variation of the TSSM population in the field and climate-controlled conditions and compared the transcriptomic and volatile profiles. Many studies have compared genotypes to reintroduce beneficial traits such as VOC emissions from wild species into domesticated lines (Bleeker et al, 2009;Mayo-Hernández et al, 2019;Paudel et al, 2019). Here, we focused on two cluster cherry tomato cultivars with similar physical (similar trichome density; Supplementary Figure 8) and agronomic traits (fruit size, shape, color, and cluster architecture), but with contrasting TSSM susceptibility to isolate chemical traits involved in mite-resistance.…”
Section: Discussionmentioning
confidence: 99%
“…However, for B. cockerelli, this relationship has not been established, although it was speculated that these compounds were involved in the repellent effect [ 39 , 40 ]. Mayo-Hernandez et al (2019) suggested that the induction of volatile organic compounds such as β-phellandrene and (+)-4-carene in an unidentified variety of wild tomato could be related to a decrease in oviposition of B. cockerelli [ 41 , 42 ]. The comparison of the metabolic profile between a susceptible variety (cv.…”
Section: Discussionmentioning
confidence: 99%
“…The tomato psyllids ( Bactericera cockerelli ) Ca Lso-positive were reared on tomato plants under greenhouse conditions [ 31 ] to induce infestation. Control plants were kept separated to avoid infestation.…”
Section: Methodsmentioning
confidence: 99%